Expansion and enhanced survival of natural killer cells expressing the killer immunoglobulin-like receptor KIR3DL2 in spondylarthritis. - Chan, A; Kollnberger, S; Wedderburn, L; Bowness, P (2005)
OBJECTIVE: The spondylarthritides (SpA) are strongly associated with possession of HLA-B27. We hypothesized that the expression of abnormal forms of HLA-B27 in SpA may have a pathogenic role through interaction with cells bearing natural killer (NK) receptors, in particular, killer immunoglobulin-like receptor (KIR) KIR3DL2, a receptor for HLA-B27 homodimer (B27(2)). We therefore undertook the present study to determine the number and function of NK and T cells bearing KIR3DL2 in SpA. METHODS: Expression of KIR3DL2 on NK and T cells was quantified in peripheral blood (PB) from 35 patients with SpA and 5 patients with juvenile enthesitis-related arthritis (juvenile ERA); samples were compared with samples from healthy and rheumatoid arthritis (RA) controls. Paired synovial fluid (SF) was studied where available. Expression of other KIRs as well as activation, memory, and homing markers on KIR3DL2+ NK and T cells was quantified. NK cell survival was assessed using the apoptotic markers annexin V and 7-aminoactinomycin D, and cytotoxicity by (51)Cr release assay. RESULTS: In SpA, an increased number of PB and SF NK and CD4+ T cells expressed the KIR3DL2 receptor compared with controls. In ERA, KIR3DL2 expression was increased in PB and SF CD4 T cells (and SF NK cells) compared with RA controls. KIR3DL2+ NK cells had an activated phenotype, and were protected from apoptosis by culture with a cell line expressing B27(2). SpA PB mononuclear NK cells from SpA patients showed greater cytotoxicity than those from controls. CONCLUSION: KIR3DL2 expression on NK cells and CD4 lymphocytes is increased in SpA and ERA. These cells are activated and may have a pathogenic role.